PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Alfa Dwi Wahyuningrum; Sunarto Sunarto (Jurnal Riset Akuntansi Politala, 2023)
This study aim to obtain empirical evidence regarding the effect of liquidity, profitability, leverage and company size on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the periode 2018 – 2021. The populations in this study are all food and beverage sub-sector manufacturing companies and beverages listed on the Indonesia Stock Exchange for the period 2018 – 2021. The sample in this study was determined using a surposive sampling technique so that 96 samples were obtained In this study the data analysis.method used multiple linear regression analyysis with SPSS. The results of this study explain that liquidity as measured by the Current Ratio (CR), profitability as measured by the Return On Assets (ROA) ratio, and company size as measured by the natural logarithm of total sales have a significant positive effect on firm value, while leverage is measured by Debt to Asset Ratio (DAR) has a significant negative effect on business value.